2023
DOI: 10.3390/brainsci13030448
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cell Ratios Are Higher in Bipolar Affective than Unipolar Depressive Disorder and Modulated by Mood Episode: A Retrospective, Cross-Sectional Study

Abstract: Immune dysregulation is implicated in the pathophysiology of both bipolar and major depressive disorder, while immune cell ratios (IRCs) have recently been proposed as clinically applicable immune biomarkers. We investigated IRCs differences in affective disorders and their association with current mood episodes and clinical features. This retrospective cohort study analyzed neutrophil–lymphocyte (NLR), monocyte–lymphocyte (MLR), and platelet–lymphocyte (PLR) ratios upon admission in 135 affective disorder in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Currently, research on the relationship between different stages of affective disorders and inflammatory ratios yields slightly disparate results. Since Koureta et al 20 found that NLR values were significantly higher only in bipolar manic episodes and MLR values were significantly higher in both stages of bipolar disorder compared to MDD, Mazza et al 8 found that manic patients had higher NLR and MLR compared to patients with unipolar and bipolar depression, with no significant difference between unipolar and bipolar depression. In clinical practice, distinguishing between bipolar and unipolar depression can be difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, research on the relationship between different stages of affective disorders and inflammatory ratios yields slightly disparate results. Since Koureta et al 20 found that NLR values were significantly higher only in bipolar manic episodes and MLR values were significantly higher in both stages of bipolar disorder compared to MDD, Mazza et al 8 found that manic patients had higher NLR and MLR compared to patients with unipolar and bipolar depression, with no significant difference between unipolar and bipolar depression. In clinical practice, distinguishing between bipolar and unipolar depression can be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Although a few studies found significantly higher NLR or MLR values in bipolar depression than in unipolar depression, most studies observed no significant difference, which is consistent with previous findings. 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that as compared to individuals with unipolar depression, bipolar manic patients exhibited a higher level of inflammation as measured by the NLR index. Additionally, it has been reported that the manic phase in BD was characterized by a higher inflammation activation, reflected by the NLR index, than the depression phase ( Dionisie et al, 2021 ; Koureta et al, 2023 ). Since neutrophils are the first line of defense for the innate immune system and lymphocytes are predominantly involved in the adaptive immunological response, elevated NLR in BD (hypo) manic episodes may indicate an imbalance in favor of innate immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Serum levels of these inflammatory biomarkers may increase or decrease with different mood episode. Meanwhile, another study ( 12 ) suggests that psychiatric disorders may have the potential to function as inducers of a wide range of immune responses, leading to a dysregulation of the inflammatory status and the cell-mediated immunity. Therefore, we speculate that these inflammatory responses may link RESLES and BD from a pathophysiological perspective.…”
Section: Introductionmentioning
confidence: 99%